Instability and protection of monolayer WS2 under heating and corona discharge conditions. (16th October 2019) - Huang, Feng; Lv, Yanfei; Zhang, Siwei; Wei, Guodan; Zhao, Shichao
Abstract: Monolayer Tungsten disulfide (WS2 ) shows unique optoelectronic properties and has potential applications in nanodevices. However, the stability of the monolayer WS2 exposed in the ambient condition should be evaluated and improved before its practical application. In this paper, we investigated the shape, structure, and luminescence of the monolayer WS2 under heating and corona discharge conditions in air. We show that monolayer WS2 without any coating film is unstable under such practical condition. To protect the monolayer, we covered a layer of polymethyl methacrylate (PMMA) on the surface of the monolayer WS2 and found the stability was improved.